IMPLEMENTATION OF INTERVISITATION TECHNIQUE THROUGH CLINICAL SUPERVISION IN IMPROVING TEACHERS’S PEDAGOGY COMPETENCE - Asep Suhendi (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2017)
The goal of this study is to improve the professionalism of teachers through clinical supervision with the approach of intervisitation techniques. Respondents taken in this action research were 40 teachers from SMA Negeri 1 Suranenggala. The research design is action research which is divided into two cycles, each cycle consists of four main activities, ie: planning, implementation, reflection and evaluation. This action research was done in the form of teaching simulation (peer teaching) by using Learning Lesson Plan (RPP) with approach of intervisitation technique. The results of the interviews obtained during the initial research meeting to determine the actions of the teachers are very motivated and enthusiastic to follow this activity. The average simulation result teaches the score of 66.68 (cycle 1) and 80,42 (cycle 2); 2) The participant attitude to the learning process simulation score 76, 69 (cycle 1) and 83.35 (cycle 2), 3) Average of Lesson Plan (RPP) score of 73.35 (cycle 1) and 82.37 (cycle 2) 4). Average teaching learning process values ??were 74.72 (cycles 1) and 84.97 (cycle 2). The conclusion of this research is academic supervision by way of clinical supervision through the approach of intervisitation technique can improve teachers’ pedagogic competence and develop their motivation to achieve in order to accelerate their teaching professionalism. The researcher recommends that similar school action research activities should be continued to be done to endorse the performance of teachers and schools achievements. Key words: Intervisitation Technique, Clinical Supervision, Pedagogy Competence